Answer:
a) 3x⁴-4x³-8x²-35x-10
Step-by-step explanation:
3x2(x²-3x-1)+5x(x²-3x-1)+10(x²-3x-1)
3x⁴-9x³-3x²+5x³-15x²-5x+10x²-30x-10
3x⁴-9x³+5x³-3x²-15x²+10x²-5x-30x-10
3x⁴-4x³-8x²-35x-10
Answer:
(f - g)(x) = -x² + 3x + 5
General Formulas and Concepts:
<u>Pre-Algebra</u>
<u>Algebra I</u>
- Function Notation
- Combining Like Terms
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x + 5
g(x) = x²
(f - g)(x) is f(x) - g(x)
<u>Step 2: Find (f - g)(x)</u>
- Substitute: (f - g)(x) = 3x + 5 - x²
- Rewrite: (f - g)(x) = -x² + 3x + 5
-24n - 30, i suggest using math.way before asking a math question aha
Answer:
A
Step-by-step explanation:
The equation of a line passing through the origin is
y = mx ( m is the slope )
To find m use the slope formula
m = ( y₂ - y₁ ) / ( x₂ - x₁ )
with (x₁, y₁ ) = (1, 1) and (x₂, y₂ ) = (- 1, - 1) ← 2 points on the line
m = = = 1
y = x ← is the equation of the line → A